The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/rheumatology/keq014
|View full text |Cite
|
Sign up to set email alerts
|

Patients with diffuse idiopathic skeletal hyperostosis do not have increased peripheral bone mineral density and geometry

Abstract: In contrast to suggestions based on DXA, pQCT revealed that DISH patients do not have increased vBMD and bone geometry in the appendicular skeleton. Ossification at tendon or ligament insertion sites may lead to overestimation of aBMD if assessed by DXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…9 Entheseal ossification and calcifications may falsely increase bone mineral density readings by dual-energy X-ray absorptiometry, but peripheral quantitative CT has shown that bone density and geometry are not altered in patients with DISH. 10 Nevertheless, CT examinations are generally rarely performed even in suspicious cases due to the associated radiation exposure. Recently, a few studies with MRI or ultrasonography (US) suggested that a local entheseal inflammatory process might precede the ossification process.…”
mentioning
confidence: 99%
“…9 Entheseal ossification and calcifications may falsely increase bone mineral density readings by dual-energy X-ray absorptiometry, but peripheral quantitative CT has shown that bone density and geometry are not altered in patients with DISH. 10 Nevertheless, CT examinations are generally rarely performed even in suspicious cases due to the associated radiation exposure. Recently, a few studies with MRI or ultrasonography (US) suggested that a local entheseal inflammatory process might precede the ossification process.…”
mentioning
confidence: 99%
“…Our results and the limited literature available [10,17] suggest that IMAT analysis protocols need further development and validation, with muscle density used in lieu of IMAT to quantify intermuscular adipose tissue content. Several recent papers report using pQCT to quantify SAT area in the lower leg [15,16,19,23,45,53,54]; however, only three studies reported precision estimates for this outcome [15,23,25]. Our lower leg and forearm precision ranged from 2.4 to 6.4% for SAT area.…”
Section: Discussionmentioning
confidence: 88%
“…DISH is more prevalent in men, and the incidence increases with age [ 15 ]. The protective effect of estrogens on the development of DISH seems to be of metabolic nature, since differences of volumetric bone density and osteoblast activity have not been seen in quantitative bone scans or functional Dickkopf-1 serum levels [ 16 18 ]. This hormonal influence is in line with associations of DISH with obesity, diabetes, hyperlipidemia, gout, hypertension and coronary artery disease as described previously [ 2 , 9 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%